The study on the morphological changes of oropharynx in patients with complete unilateral cleft lip and palate after palatopharyngeal closure - Chen, Baitong; Zhang, Hongchuang (Frontiers in Neuroscience, 2022)
Cleft lip and palate can be treated as one of the most common craniofacial congenital malformations in humans. Such disease has influences on tens of millions of patients in all over the world. Cleft lip and palate deformity affects many important physiological functions including breathing, swallowing, speech, chewing, and aesthetics. This work focus on researching the morphology and airway volume of oropharynx patients with unilateral complete cleft lip and palate after palatopharyngeal closure. Meanwhile, this work evaluated the similarities and differences between patients with cleft lip and palate and those without such issue. The employed data, which selected from the Department of Stomatology of Xuzhou first people's Hospital, are the conical beam CT. Meanwhile, it was pointed that the selected experimental group, who confronted the cleft lip, cleft palate and velopharyngeal closure surgery, and the selected control group, who are health children at the corresponding age. The parameters, including the airway volume, the airway volume of velopharyngeal and oropharyngeal segments, the minimum cross-sectional area of pharynx, the horizontal plane airway area of hard palate and soft one, the horizontal airway area of hyoid bone and the vertical distance between hard palate and soft one, can be measured by Dolphin. And then, those parameters analyzed with the statistically approach. With the analysis the above-mentioned parameters, we can find that the airway volume, minimum cross-sectional area of pharynx, horizontal cross-sectional area of hyoid and distance between hard palate and soft palate tip between patients with complete unilateral cleft lip and palate are significant differences between the experimental group and the control one. Meanwhile, other left parameters, including the horizontal cross-sectional area of airway in the horizontal plane of hard palate and the horizontal plane of soft palate, can hardly show the differences in the two group. The patients, who confronted the unilateral complete cleft lip and palate, can improve with the velopharyngeal closure surgery. It is hardly neglected that the length and vertical distance of soft palate and the volume of each segment of airway are still differences between the experimental group and the control one.